Trends in Publication and Levels of Evidence in Foot & Ankle International From 2000 to 2015. Issue 3 (27th July 2020) - Griffith, Matthew; Han, Edward; Hattaway, Joshua; Huh, Jeannie
Background: As the movement toward evidence-based medicine grows and publication rates rise each year, critical analysis of the orthopedic literature has become increasingly important. To aid readers in assessing the scientific quality of published research, Foot & Ankle International ( FAI ) began assigning levels of evidence to all clinical articles in 2008. The purpose of this study was to analyze trends in the characteristics and levels of evidence of articles published in FAI between 2000 and 2015. Methods: All articles published in FAI from the years 2000, 2005, 2010, and 2015 were reviewed and categorized into article type (clinical, basic science, review, or technical tip). Each clinical article was assigned a level of evidence (I-V) and study type (prognostic, therapeutic, economic, or diagnostic). Descriptive information was gathered pertaining to country of origin, author credentials, and funding. Statistical analysis was performed using chi-squared tests to detect any trends in levels of evidence and publication characteristics. Results: A total of 647 articles were reviewed. From 2000 to 2015, there was a statistically significant increase in the publication of clinical research articles (70% to 83%; P = .013), while the number of basic science articles decreased (29% to 17%; P = .013). Of the clinical articles, there was a significant increase in therapeutic studies (41% to 58%; P = .003). During the study period, the publication of Level I and II evidence significantly increased (2% to 14%; P = .002). Although Level III and V evidence also increased (65% to 71%, P > .99), this was not found to be statistically significant. Publications originated from a total of 39 countries, with a significant increase in the proportion of international papers (33% to 48%; P = .007) over the study period. The proportion of articles authored by Doctors of Podiatric Medicine (DPMs) during the study period significantly decreased (4% to 2%, P = .035). Finally, the percentage of studies that disclosed the use of outside funding increased during the study period, with reported funding from grants or professional groups rising from 3% to 16% ( P < .001) and reported funding from commercial sources rising from 0% to 9% ( P = .002). Conclusion: The proportion of Level I and II studies published in FAI significantly increased from 2000 to 2015. The publication of clinical research rose, with a majority being therapeutic studies. There was a significant increase in articles published by international authors and a significant decrease in articles published by DPMs. During the same time period, there was a rise in the proportion of articles reporting the use of outside funding, both professional and commercial.